Pengaruh Kehandalan Pegawai dan Fasilitas Terhadap Brand Image dan Implikasinya pada Loyalitas Pasien di Rumah Sakit Umum Natama Kota Tebing Tinggi - Devi Juni Anisah Simare Mare; Ade Trianty; Eka Mayastika; Limega Candrasa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the Influence of Employee Reliability and Facilities on Brand Image and Its Implications on Patient Loyalty at Natama General Hospital, Tebing Tinggi City. The research method used is a quantitative method using the help of Smart PLS version 3.0 which was collected from the results of distributing questionnaires to Patients at Natama General Hospital. The analysis method used in this study is to use an instrument test, namely a validity and reliability test. measurement model (outer model) namely validity test, reliability test, then structural model (inner model) including: coefficient of determination / r-square (r2), goodness of fit model and hypothesis testing with t-statistic test and indirect effect test (indirect effect). The results of SPSS in this study are Employee Reliability Does Not Affect Brand Image, Facilities Affect Brand Image, Employee Reliability Does Not Affect Patient Loyalty, Facilities Affect Patient Loyalty, Brand Image Does Not Affect Patient Loyalty, Brand Image Cannot Mediate the Relationship Between Facilities and Patient Loyalty, Brand Image Cannot Mediate the Relationship Between Reliability and Patient Loyalty.